EFFECTS OF DIPLOMATIC RELATIONS ON ECONOMY OF CHINA - SERFRAZ, AYESHA (IJRDO - Journal of Business Management, 2016)
This study is a detailed discussion and analysis of china’s economy. The purpose of this study is to discuss China’s diplomatic relations with rest of the world and to determine that how it is becoming the fastest growing economy. No econometric tests have been applied, it is a thorough and comprehensive study of China’s political, economic and diplomatic policies. History of China has been discussed under different political regimes with an in depth analysis of five year plans. Presently, China is the fastest growing economy and it is maintaining peace with rest of the world to concentrate on development policies. Military built up of China has been analyzed and a comparison has been made between past and present military force. Special emphasis has been given towards Pakistan and China relations in accordance with Pakistan-China economic Corridor.